A physicist's approach to COVID-19 transmission via expiratory droplets (2020)
In this paper, a physicist's approach is given to support the necessity to wear surgical masks during the COVID-19 pandemics; they have become compulsory in Eastern countries, while in Western countries they are still an optional. My thesis is supported and described on the basis of a physicist's model which studies the droplets behavior when emitted by the respiratory apparatus of an infected person, symptomatic or not. The intermediate dimensioned droplets are proved to be changed into aerosol, losing their water content and becoming seriously contagious, but in their initial phase they could be easily caught by a simple surgical mask. The actual efficiency of FFP3 masks has been examined and found to be lower than expected.